Time discretization sensitivity analysis for a rod ejection transient scenario in a generic SMR concept using Serpent/SUBCHANFLOW - Huaccho Gianfranco; Sánchez-Espinoza Victor Hugo; Mercatali Luigi (EPJ Web of Conferences)
This paper analyses a control rod ejection transient scenario in a generic SMR concept using the multi-physics coupling tool which includes the Monte Carlo Serpent code (developed at VTT, Finland) and the subchannel thermal-hydraulic code SUBCHANFLOW (developed at KIT, Germany). A Hot Zero Power state (HZP at 330 W) is considered for the initial condition. A control rod assembly located in the peripheral part of the core is ejected in 0.05 s, inserting a reactivity of ~1.4$ into the system and producing a fast excursion of the power in an asymmetric shape, achieving a peak power ~107 times bigger than the initial state. The thermal-hydraulic feedback then controls the prompt-critical condition, achieving a subcritical state. The analysis is restricted to one second time evolution, and a sensitivity analysis on the time discretization using different time bins is performed. The results show how the use of different time discretizations impact the prediction of the main safety parameters’ evolution, with differences up to ~50% in peak power, ~100 °C in fuel temperature, ~20 °C in cladding temperature, and ~40% in DNB ratio. For this particular problem, it is concluded that shorter time bins are needed; minimum differences in terms of temperatures were observed when using 1 ms and 0.5 ms bins, suggesting that time bins of these orders are appropriate for the type of scenario analyzed in this work.